Sensing the border(s): sound and carceral intimacies in and beyond indefinite detention - de Souza, Poppy (Crime, media, culture, 2023)
This article examines a sound-based digital project co-created with refugees and asylum seekers held in indefinite detention in Australia and Papua New Guinea to advance understandings of the sensory violence of borders ? and resistance to borders ? and their reordering of intimate realms. In where are you today (2020), refugees/asylum seekers catalogued their carceral environments in 10-minute sonic vignettes which were distributed to listeners daily via text message, for 30 consecutive days. Drawing on sensory methodologies and feminist orientations towards the intimate, the article considers how this sound project alerts us to an alternative sensory politics attuned to the quiet, quotidian and exhausting labour of resisting Australia?s racialised border regime. Through a close listening to selected recordings, we argue the intimacies shared through where are you today produce knowledge about embodied practices of care, breath, touch and waiting in indefinite detention. Networked, transborder sound projects can unsettle both incarcerated and non-incarcerated subjects? relationships to their environments, opening affiliative possibilities for coming into relation with the border(s) in new ways. We conclude that the project?s creators forge and sustain carceral intimacies within and despite the border?s affective violence, and that sound is a particularly affective and evocative means of conveying and creating these intimacies, in and beyond indefinite detention.